Minority Persecution in Bangladesh's Authenticity of Human Rights Violations and the Influence of Homemade Craft, Artwork, and Culture: A Case Study from North-Western Bangladesh - Mst. Baly Khatun; Yasmin Ara Ema; Tania Afroz; Sharmin Akatar Sompa; Md Wasim Akram; Md. Romjan (Penerbit Hellow Pustaka, 2025)
Within the context of Bangladesh's minority populations, this study investigates the interconnections of religious persecution, awareness of human rights, and cultural resilience. The findings, which are based on survey data collected from a wide pool of respondents, indicate that 36.6% of the participants reported having experienced religious persecution, with verbal threats being the most common form of such persecution. On the other hand, only 18.9% of respondents had ever reported events of this nature, and even fewer obtained answers that were effective. The percentage of people who were aware of their legal rights was low (48%) and the level of trust in authorities and access to legal help remained poor. In spite of these obstacles, cultural practices including as music, needlework, and bamboo crafts were retained to a large extent, with 65.7% of the population actively participating in traditional art forms. Despite the fact that 70.7% of respondents agreed that cultural preservation helps establish identity, youth engagement was low (35.4%), and public recognition and institutional support were modest. A significant contribution that traditional culture makes to the development of resilience in the face of systematic marginalization is highlighted in this study. For the purpose of empowering communities, preserving cultural legacy, and protecting minority rights in the face of political and societal impediments, it advocates for more legal support, public forums, and focused training.